Histogram analysis of stretched‐exponential and monoexponential diffusion‐weighted imaging models for distinguishing low and intermediate/high gleason scores in prostate carcinoma - Liu, Wei; Liu, Xiao H.; Tang, Wei; Gao, Hong B.; Zhou, Bing N.; Zhou, Liang P. (Journal of magnetic resonance imaging, 2018)
Background Noninvasive measures to evaluate the aggressiveness of prostate carcinoma (PCa) may benefit patients. Purpose To assess the value of stretched‐exponential and monoexponential diffusion‐weighted imaging (DWI) for predicting the aggressiveness of PCa. Study Type Retrospective study. Subjects Seventy‐five patients with PCa. Field Strength 3T DWI examinations were performed using b‐values of 0, 500, 1000, and 2000 s/mm2. Assessment The research were based on entire‐tumor histogram analysis and the reference standard was radical prostectomy. Statistical Tests The correlation analysis was programmed with Spearman's rank‐order analysis between the histogram variables and Gleason grade group (GG). Receiver operating characteristic (ROC) regression was used to analyze the ability of these histogram variables to differentiate low‐grade (LG) from intermediate/high‐grade (HG) PCa. Results The percentiles and mean of apparent diffusion coefficient (ADC) and distributed diffusion coefficient (DDC) were correlated with GG (ρ: 0.414–0.593), while there was no significant relation among α value, skewnesses, and kurtosises with GG (ρ:0.034–0.323). HG tumors (ADC:484 ± 136, 592 ± 139, 670 ± 144, 788 ± 146, 895 ± 141 mm2/s; DDC: 410 ± 142, 532 ± 172, 666 ± 193, 786 ± 196, 914 ± 181 mm2/s) had lower values in the 10th, 25th, 50th, 75th percentiles and means than LG tumors (ADC: 644 ± 779, 737 ± 84, 836 ± 83, 919 ± 82, 997 ± 107 mm2/s; DDC: 552 ± 82, 680 ± 94, 829 ± 112, 931 ± 106, 1045 ± 100 mm2/s). However, there was no difference between LG and HG tumors in α value (0.671 ± 0.041 vs. 0.633 ± 0.114), kurtosises (ADC 0.09 vs. 0.086; DDC –0.033 vs. –0.317), or skewnesses (ADC –0.036 vs. 0.073; DDC –0.063 vs. 0.136). The above statistics were P < 0.01. ADC10 with AUC = 0.840 and DDC10 with AUC = 0.799 were similar in discriminating between LG and HG PCa at P < 0.05. Data Conclusion Histogram variables of DDC and ADC may predict the aggressiveness of PCa, while α value does not. The abilities of ADC10 and DDC10 to discriminate LG from HG tumors were similar, and both better than their respective means. Level of Evidence: 3 Technical Efficacy: Stage 1 J. MAGN. RESON. IMAGING 2018;48:491–498.